Perbedaan Penurunan Kadar Gula Darah pada Kelompok Yang Diberi Terapi Jus Buah Naga Merah dan Bengkuang pada Penderita DM di Komunitas Gres Lansia Kabupaten Tuban - Dwi Fitri Hariyanti; Dwi Kurnia PS; Lilia Faridatul Fauziah (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Diabetes Mellitus (DM) is a metabolic disorder in which the body's inability to oxidize carbohydrates is found, due to disturbances in the mechanism of insulin action which can cause hyperglycemia, glycosuria, polyuria, acidosis, lipemia, and ketonuria. Research objectives to analyze the difference in decreasing blood sugar levels in the group that was given red dragon fruit juice and jicama therapy in DM sufferers in the elderly GRES community in Tuban Regency. The design of this research is true experimental design, Two Group Pre-test and Post-test Design. The sample in this study were the elderly in the GRES Community, Tuban Regency, totaling 34 elderly people, using a purposive sampling technique. The analysis of this study used the statistical test pair T-test and Independent T-test. The results of the study using the Paired T-Test showed that the red dragon fruit group had a p-value of 0.000 <0.05, which means that H1 was accepted, that is, there was a difference in decreasing blood sugar levels before and after being given red dragon fruit juice therapy and the jicama juice group. with a p-value of 0.000 <0.05 which means that H1 is accepted, that is, there is a difference in the decrease in blood sugar levels before and after being given Jicama juice therapy.